Contribution of steel sheeting to the vertical shear capacity of composite slabs. (October 2019) - Pereira, Miguel; Simões, Rui
Abstract: The real capacity of steel-concrete composite slabs currently used in buildings tends to be governed by the longitudinal shear failure mode. However, in many cases, the design of these structural members according to Eurocode 4, Part 1.1 (EN 1994-1-1) is governed by the vertical shear capacity. The design methodology for the determination of the vertical shear resistance predicted in the referred standard underestimates the shear resistance of steel-concrete composite slabs because it is based on the design model for reinforced concrete slabs stated in Eurocode 2, Part 1.1 (EN 1992-1-1), does not take the contribution of the profiled steel sheeting into account adequately. The results of an experimental programme, comprising 4 experimental tests on short-span steel-concrete composite slabs and carried out at the Department of Civil Engineering of the University of Coimbra, Portugal, are then shown and discussed. In order to induce a failure by vertical shear, the composite slabs tested were provided with a longitudinal shear reinforcement system composed by transversal bars crossing longitudinal stiffeners placed along the upper flange of the steel sheets. The results of the experimental tests were also used to calibrate numerical models, which made it possible to carry out a parametric analysis. The experimental and numerical results showed that the design methodology prescribed by Eurocode 4, Part 1.1 is quite conservative as it underestimates the relevant contribution of the resistance of the profiled steel sheeting to the slab's vertical shear capacity. Highlights: Design methodology of Eurocode 4, Part 1.1 underestimate the vertical shear capacity of composite slabs. Improvement of the design models for vertical shear resistance of steel-concrete composite slabs. Contribution of steel sheeting for the vertical shear resistance. Experimental evaluation of the vertical shear resistance of steel-concrete composite slabs. Numerical evaluation of the vertical shear resistance of steel-concrete composite slabs.